Analisa Tingkat Kepuasan Civitas Akademika terhadap Kinerja BEM pada STMIK Widuri Menggunakan Metode Service Quality - Nanda Fauzy Siddiq; Rouli Doharma (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The rapid development of science and technology has driven increasingly intense global competition, demanding educational institutions to play an active role in developing human resources (HR). Higher education serves as a platform to enhance students' competitiveness, not only through academic education but also through student organizations such as the Student Executive Board (BEM). This organization provides opportunities for students to develop social skills, leadership, and other soft skills that are highly essential in the professional world. STMIK Widuri, as one of the higher education institutions in Indonesia, integrates academic education with students' personal development through organizations like BEM. This study aims to evaluate the level of satisfaction among the academic community regarding activities organized by the BEM of STMIK Widuri during the 2023–2025 period using the Service Quality (SERVQUAL) approach. This method measures service quality based on five key dimensions: reliability, responsiveness, assurance, empathy, and tangible aspects. Data were collected through interviews, observations, questionnaires, and literature reviews, with a total of 51 respondents comprising students, lecturers, and staff. The results of the study indicate that all data are valid and reliable based on the Cronbach Alpha test, with values exceeding 0.6. Analysis using SPSS software shows a gap between respondents' perceptions and expectations of the services provided by BEM. These findings are expected to provide insights for the BEM of STMIK Widuri to improve service quality and design programs that better align with the needs of the academic community. Thus, BEM's role as a facilitator of student potential development can be further optimized, supporting the achievement of STMIK Widuri's vision as a globally competitive educational institution.